ASSESSMENT OF AUTOCRATIC LEADERSHIP BEHAVIOUR OF COACHES ON ATHLETES IN INDIVIDUAL AND TEAM SPORTS IN NIGERIA - Ali, I. D. (FUDMA JOURNAL OF SCIENCES, 2023)
This study assessed coaching leadership behaviour preference by athletes in individual and team sports that will lead to increased satisfaction and performance. The Ex-post facto research design was employed since the design is based on existing information which could be manipulated. A structured questionnaire was used to collect data for this study. A total of nine hundred and sixty (960) copies of questionnaire was distributed to athletes in selected States Sports Councils using the simple random sampling procedure. The data collected were subjected to statistical analysis using frequency and percentages for the demographic characteristics of the respondents. The two samples Z-test was used to test the hypothesis. The hypothesis was tested at 0.05 level of significance. The findings of the study revealed: That athlete in team and individual sports did not have preference for coaches disposed towards autocratic behaviour. The following recommendations were made: Coaches should not engage in autocratic behaviours when coaching. Autocratic behaviours should not be adopted by coaches for increase in athletes’ satisfaction and enhancement in performance.
Keywords: Assessment, Autocratic Leadership, Athletes, Behaviour, Coaches